2014
DOI: 10.1523/jneurosci.5183-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

GluN3A Promotes Dendritic Spine Pruning and Destabilization during Postnatal Development

Abstract: Synaptic rearrangements during critical periods of postnatal brain development rely on the correct formation, strengthening, and elimination of synapses and associated dendritic spines to form functional networks. The correct balance of these processes is thought to be regulated by synapse-specific changes in the subunit composition of NMDA-type glutamate receptors (NMDARs). Among these, the nonconventional NMDAR subunit GluN3A has been suggested to play a role as a molecular brake in synaptic maturation. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 36 publications
1
37
2
1
Order By: Relevance
“…; Kehoe et al . ). Our data are the first to suggest that GluN3A may contribute to activity‐dependent synapse development by modulating NMDAR‐dependent changes in gene transcription.…”
Section: Discussionmentioning
confidence: 97%
“…; Kehoe et al . ). Our data are the first to suggest that GluN3A may contribute to activity‐dependent synapse development by modulating NMDAR‐dependent changes in gene transcription.…”
Section: Discussionmentioning
confidence: 97%
“…Some examples include knockout of components of the major histocompatibility complex (MHC1), where LTD and/or ocular dominance plasticity are also impaired 94,95,113115 , and deletion of different subunits of NMDARs, which results in increases in synapse number 93,116119 (but see 120 ). However, whether these manipulations impact development of synapses or whether they directly prevent synapse pruning is often ambiguous 121123 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with recent studies supporting a critical role for p75 NTR in hippocampal-dependent synaptic plasticity (10,108), normalization of hippocampal p75 NTR levels in distinct HD mouse models with genetic or pharmacological approaches rescues hippocampal synaptic plasticity, memory deficits and dendritic spine alterations, likely by normalization of the RhoA GTPase activity (28,190). Overall, this evidence suggests that antagonism of p75 NTR could represent an excellent approach to promote BDNF-mediated signaling in HD corticostriatal pathway, thereby restoring corticostriatal connectivity (227), ameliorating hippocampal synaptic dysfunction and memory deficits (135) and improving cell survival (29). An important consequence of these findings is that whereas TrkB is widely and robustly expressed in the adult brain, p75 NTR has a restricted tissue distribution, and its expression is developmentally downregulated in most parts of the brain, which makes the targeting of p75 NTR likely to have fewer side effects in HD patients.…”
Section: Therapeutic Strategiesmentioning
confidence: 93%
“…PACSIN1 controls the endocytic removal of GluN3Acontaining NMDARs (224). GluN3A is highly expressed in the brain during early postnatal development to prevent premature synapse plasticity and stabilization, but its expression declines afterwards (135,179,247,328). Nevertheless, a recent study found that mutant huntingtin binds to and sequesters PACSIN1, causing its subcellular redistribution away from the synapse and promoting accumulation of GluN3A-containing NMDARs at the surface of striatal neurons.…”
Section: Glun3amentioning
confidence: 99%